Study of the Potential of the Capsule Shell Based on Natural Polysaccharides in Targeted Delivery of the L-Phenylalanine Ammonia-Lyase Enzyme Preparation - Olga Babich; Lyubov Dyshlyuk; Alexander Prosekov; Svetlana Noskova; Oksana Ivina; Valery Pavsky; Svetlana Ivanova; Olga Bulgakova (MDPI AG, 2020)
The treatment of classical phenylketonuria is currently represented by many new methods of disease management. A promising method is the use of the enzyme L-phenylalanine ammonia-lyase (PAL) in various forms. The widespread use of enzyme preparations in therapy is limited by a lack of understanding of the mechanisms and systems of the targeted transport of PAL into certain organs and tissues as a result of the incorporation of a drug into the carrier. To ensure the stability of enzymes during the delivery process, encapsulation is preferable, which, as a rule, ensures the preservation of the qualitative characteristics of the enzymes orally applied to the environmental effects of the gastrointestinal tract (acidity, temperature, oxidation, etc.). Capsule preparations showed sufficient stability in the model gastric fluids and sustained release of the drug in the simulated intestinal fluid. Currently, there is a wide range of polymers used for encapsulation. The use of natural sources in the production technology of capsule systems improves bioavailability, controls the release, and prolongs the half-life of active substances. The advantage of this method is that the used enzyme is completely protected by the cell membranes of the capsules, which preserve its stability in the aggressive environment of the gastrointestinal tract. Capsules were obtained on the basis of compositions of hydrocolloids of plant origin. The potential of the developed capsules for targeted delivery of the enzyme preparation was studied. The degradation of the encapsulated form of the PAL enzyme preparation was studied in vitro in model bio-relevant media simulating the gastric and intestinal environment. The dynamics of the breakdown of the capsule shell allow us to expect that the release of L-phenylalanine ammonia-lyase from capsules based on plant hydrocolloids will occur no earlier than reaching the upper intestines, where the interaction with the protein components of the consumed food products to neutralize phenylalanine should occur.